Orthodontically Induced Root Resorption-An Updated Review - Karkazi Frantzeska; Lysy Juraj; Bitsanis Elias; Tsolakis Apostolis (Balkan Stomatological Society, 2020)
Background/Aim: Root resorption is one of the most common consequences of orthodontic treatment. However, its mechanism, etiology factors, diagnostic methods and the possibility of root repair remain controversial topics. The aim of this paper is to provide an updated review of the current literature concerning the orthodontically induced root resorption.